INDONESIAN LANGUAGE LEARNING FOR NON-NATIVE SPEAKERS THROUGH ONLINE MUSIC AND LEARNER ASSESSMENT - Defina, Defina; Anggradinata, Langgeng Prima (Jurnal Salaka : Jurnal Bahasa, Sastra, dan Budaya Indonesia, 2025)
COVID-19 has led to BIPA learning being conducted online via the Zoom platform. To prevent BIPA learners still in their respective countries from becoming bored with their lessons, providing song material is necessary. The purpose of this study is to describe the implementation of BIPA learning through music media, students' assessment of the impact of songs in BIPA learning, and students' brief statements about the song material. This research is a descriptive qualitative study involving questionnaires given to 12 BIPA KNB IPB 2021/2022 students. The results indicate that students agree to include song material in BIPA levels 2 and 3, with various genres at least once a week, to boost motivation, reduce tension, and make learning more enjoyable. Songs can help train listening and pronunciation skills, improve mastery of vocabulary, grammar, and word meanings, and provide insight into Indonesian culture. The recommended number of songs is two per meeting. The implication of this research is that song material can be integrated into BIPA lessons, but no more than two songs should be used.